Risk factors for drug-related acute pancreatitis: an analysis of the FDA adverse event reporting system (FAERS) - Zhang, Lin; Mao, Wei; Liu, Dan; Hu, Bin; Lin, Xiaofang; Ran, Jie; Li, Xingxing; Hu, Jing (Frontiers in Pharmacology, 2023)
Objective: While several drugs have been linked to acute pancreatitis (AP), the AP-related risk of most drugs remains unclear. This study investigated the risk factors for drug-induced AP by analyzing a large dataset from the FDA Adverse Event Reporting System (FAERS). Methods: The reporting odds ratios (ROR) were used to assess the reports of drug-induced AP from the first quarter of 2004 to the second quarter of 2022. Single-factor, LASSO, and multi-factor regression analysis were performed to explore drug-related AP-related risk factors. Bonferroni correction was applied for the multiple comparisons performed. Results: A total of 264 drugs associated with AP, including antineoplastic drugs (35/264), antidiabetic drugs (28/264), antibacterial drugs (24/264), immunomodulatory drugs (11/264), antipsychotic drugs (6/264), and other drugs (160/264) were retrieved. Multi-factor analysis showed that males, age 41-54 years old, and 36 drugs, including Tigecycline, were risk factors for drug-related AP. The median time to drug-related AP onset was 31 days (interquartile range [IQR] 7–102 days) and about 75% of adverse events occurred within 100 days. Conclusions: These findings may help clinicians to identify drug-related AP at the early stage and can be used to inform future studies of drug-related AP pathogenesis.